Autoevaluación de la práctica pedagógica docente en estrategias para promover aprendizajes significativos en el aula en las instituciones educativas de nivel primaria I.E.P. Elzeario Mac Donald E I.E.P. N° 60078, Pebas 2021 - Villacorta Ahuanari, Llarne (2024)
The importance of the study was to know how the teacher himself rates himself in the use of strategies to promote meaningful learning in the classroom, as an answer to the question: What is the level of self-evaluation of the teaching pedagogical practice in strategies to promote meaningful learning in the classroom in the Primary Level Educational Institutions I.E.P. Elzeario Mac Donald and I.E.P. N° 60078 Pebas 2021? The descriptive, cross-sectional, univariate, field type was designed as a methodology to apply and the 101 primary teachers from both institutions were considered as population and sample. A questionnaire prepared for this purpose and validated by expert professionals was applied through a survey. The research shows that the level of self-evaluation of the teaching pedagogical practice in strategies to promote meaningful learning in the classroom, in most of the teachers (63.4%) is at a good level, which indicates a pedagogical approach focused on fostering meaningful learning. However, 33.7% are at a regular level, which indicates that they need to improve in the implementation of significant strategies.